Intrinsic viscosity of aqueous solutions of carboxymethyl guar in the presence and in the absence of salt - Badiger, Manohar V.; Gupta, Nivika R.; Eckelt, John; Wolf, Bernhard A. (Macromolecular Chemistry and Physics, 2008)
Intrinsic viscosities were determined for solutions of CMG in pure water and 0.9 wt.-% aqueous NaCl. To avoid the 0/0-type extrapolation typical for Huggins plots, a new procedure was used. For CMG and pure water, this requires only two adjustable parameters: the specific hydrodynamic volume of the polymer in the limit of infinite dilution and a hydrodynamic interaction parameter. The intrinsic viscosity of CMG (no salt) at room temperature is 6 050 mL . g(-1); approximately half as large as that of Na-PSS of comparable molar mass. The ratio of the intrinsic viscosities with and without salt is approximate to 7 for CMG, as compared to >100 for Na-PSS. The reasons 1:5 5 for the different behaviors of the two types of polyelectrolytes are being discussed.
Keywords: Biopolymers; Carboxymethyl guar; intrinsic viscosity; polyelectrolyte; salt-free solutions

Influence of hydrophilic/hydrophobic diols on the properties of polyurethane hydrogels: solvent-free one-pot synthesis - Divakaran, Anumon V.; Nair, Sanoop B.; Karambe, Shivani S.; Wadgaonkar, Prakash P.; Nair, Kiran Sukumaran; Badiger, Manohar V. (Journal of Materials Chemistry B, 2025)
Herein, we report the design and synthesis of bio-degradable porous polyurethane hydrogels by a green, solvent-free, one-pot technique that can withstand physiological mechanical loads and aid in tissue regeneration. The hydrophilic/hydrophobic nature of the hydrogel was tuned using diols such as polycaprolactone diol (PCL) and polycarbonate diol (PCD), in combination with polyethylene glycol (PEG, MW approximate to 4000 g mol-1), 4,4 `-methylene bis(cyclohexyl isocyanate) (H12MDI) and hexanetriol (HT), which served as crosslinking agents. The structural characterizations of the hydrogels were performed using FT-IR as well as 1H and 13C high resolution magic angle spinning nuclear magnetic resonance (HR-MAS) spectroscopy. The utilization of various diols in the synthesis of the hydrogels enabled precise control over crystallinity, pore sizes, and customization of mechanical and degradation properties. These hydrogels exhibited tensile strength in the range of 0.22-1.48 MPa, while their compressive strength varied from 0.92 to 29.3 MPa. In vitro degradation profiles in the presence and absence of the enzyme Amano lipase PS revealed that the degradation process is contingent upon the specific diol present in the hydrogel. Furthermore, preliminary in vitro biological experiments confirmed the biocompatibility of the gels, indicating their potential as suitable substrates for drug delivery applications. This diverse library of gels can be shaped into specific forms, highlighting their promising applications as scaffolds and implants in drug delivery systems and tissue engineering.

Insight Into the Influence of Salinity on Flow and Flocculation Behavior of Acrylamide-Based Cationic Polyelectrolyte - Ranganath, Suresha P.; Kurian, Rachna; Torris, Arun; Khairnar, Ajay; Ravindranathan, Sapna; Rajamohanan, P. R.; Badiger, Manohar V.; Wolf, Bernhard A. (Journal of Applied Polymer Science, 2026)
The viscometric behavior of aqueous solutions of acrylamide and acrylamidopropyl trimethylammonium chloride copolymers (AM-co-APTMAC) with varying cationic content under different salinity conditions was studied. Viscometric measurements were employed to determine intrinsic viscosity and quantify the influence of electrostatic interactions on chain conformation. Rheology experiments were performed to probe dynamic flow behavior under shear to obtain insights into polyelectrolyte viscoelastic properties under conditions mimicking industrial processes. Viscometric and rheology data analysis is augmented with insights from NMR relaxation and pulsed field gradient NMR diffusion experiments. Further, flocculation of kaolin suspensions was studied using aqueous solutions of AM-co-APTMAC copolymers with different charge fractions in the presence and absence of salt. The physicochemical insights on the behavior of AM-co-APTMAC polyelectrolytes in solution from this study could be relevant in practical applications, such as plants that use seawater or in cases where the ionic strength of suspensions is high due to salinity in the medium.
Keywords: copolymers; polyelectrolytes; structure property relationships; theory and modeling